Environmental nanopollutants : sources, occurrence, analysis and fate - Szpunar, Joanna; Jiménez-Lamana, Javier (Cambridge : Royal Society of Chemistry, 2022)
Offering a wide overview of the most recent research on environmental nanopollutants this book gives the reader a full picture of the research on nanoparticles in the environment.
3.3 Mass Concentration and Chemical Compositions -- 3.3.1 Physical Characteristics of Nanoparticles -- 3.3.2 Chemical Characteristics of Nanoparticles -- 3.3.3 Source Apportionment -- 3.4 Nanoparticles and Health Effects -- 3.4.1 Toxicokinetics of Nanoparticles -- 3.4.2 Excretion and Clearance of Nanoparticles -- 3.4.3 Health Effects -- 3.4.4 Big Data Analysis and a Case Study in Thailand -- 3.5 Conclusion -- Acknowledgements -- References -- Chapter 4 Investigation of Airborne Nanoparticles: The Focus on Analytical Chemistry -- 4.1 Introduction -- 4.2 Origin and Sources of Nanoparticles
Print version record.
eBooks on EBSCOhost
Keywords: Nanoparticles -- Environmental aspects; Environmental chemistry; Nanoparticules -- Aspect de l'environnement.; Chimie de l'environnement.; Environmental (see also Environmental Science); Environmental Conservation & Protection; NATURE; Nanotechnology & MEMS; TECHNOLOGY & ENGINEERING; Chemistry; SCIENCE; Environmental chemistry; Electronic books